TINJAUAN YURIDIS BENTUK PERLINDUNGAN INVESTOR OLEH MANAJER INVESTASI DALAM MENGELOLA REKSA DANA - Mega Kartika; Julian Parningotan; Jonni Josua Lumbantobing; Yoseph Imando P Hutahaean; Julianus Jesaya Purba (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Mutual funds are a place to collect funds from people who want to invest, then these funds are used for further investment by the Investment Manager into a stock portfolio. Mutual Fund management is carried out by the Investment Manager in accordance with the agreement in the form of a Collective Investment Contract and the Company. The Financial Services Authority provides legal protection to investors in the capital market by issuing Financial Services Authority Regulation No.10/POJK.04/2018 concerning Implementation of Investment Manager Governance and Financial Services Authority Regulation No.24/POJK.04/2014 concerning Guidelines for the Implementation of Functions -Function of Investment Manager which is the implementing regulation of Law Number 21 of 2011 concerning the Financial Services Authority. This study aims to study and understand the forms of protection for investors provided by Investment Managers when managing Mutual funds.